دور ماراثون مسقط في تعزيز المشاركة الرياضية وبعض الجوانب الاجتماعية والنفسية وصورة الوجهة لدى المشاركين - قمادة، نبيل محمود; الدروشي، عبدالرحيم بن مسلم بن خلفان; اليعربي، علي بن سلام; العجمي، إيناس أحمد (جامعة حلوان - كلية التربية الرياضية للبنات, 2023)
هدفت الدراسة الحالية إلى التعرف على دور ماراثون مسقط في تعزيز المشاركة الرياضية وبعض الجوانب الاجتماعية والنفسية وصورة الوجهة لدى المشاركين. ولتحقيق أهداف الدراسة قامت الباحثة بالاعتماد على المنهج الوصفي المسحي وذلك لملائمته لطبيعة الدراسة. حيث تم اختيار العينة عن طريق العينة المتاحة ممن تطوعوا بالاستجابة لأداة الدراسة وبلغ عددها ۲۰۰. تم استخدام الاستبانة كأداة لجمع البيانات حيث احتوت على ثلاثة محاور؛ المحور الأول الذي يقيس المشاركة الرياضية (أثر المشاركة قبل وبعد الحدث) وتكون من (۹) فقرات، والمحور الثاني الذي يقيس التأثيرات الاجتماعية والنفسية (الترابط الاجتماعي وتقدير الذات) وتكون من (۱۰) فقرات، والمحور الثالث الذي يقيس صورة الوجهة (الصورة المعرفية والصورة العاطفية) وتكون من (۱۱) فقرة. أوضحت النتائج وجود أثر إيجابي طويل المدى على مستوى المشاركة الرياضية، وذلك إلى جانب الأثر الاجتماعي من خلال الترابط الاجتماعي، والأثر النفسي من خلال تقدير الذات بعد خوض تجربة ماراثون مسقط. كما نجح ماراثون مسقط في وضع بصمة ذهنية وعاطفية لدى المشاركين. توصلت الدراسة إلى العديد من التوصيات أهمها أن تقوم الهيئات الرياضية المحلية المنظمة للأحداث الرياضية بالاهتمام بمثل هذه الأحداث في الفترة الراهنة وذلك لعدم امتلاك الموارد اللازمة لاستضافة أحداثا ضخمة في سلطنة عمان، ووضعها كقاعدة يتم من خلالها تطوير العمل باستراتيجيات تصل إلى تحقيق الأهداف المرجوة. The current study aimed to identify the role of the Muscat Marathon in promoting sports participation and other social and psychological aspects among the participants beside the image of the destination. To achieve the objectives of the study, the researcher relied on the descriptive survey method, due to its suitability to the nature of the study. The sample was selected by means of the available sample who volunteered to respond to the study tool, and their number was 200. The questionnaire was used as a tool for data collection, as it included three dimensions. The first dimension measures sports participation (the impact of participation before and after the event), and it consisted of (9) paragraphs. The second dimension measures the social and psychological effects (social bonding and self-esteem) and it consisted of (10) items. The third dimension measures the image of the destination (the cognitive image and the emotional image) and it consists of (11) items. The results showed a long-term positive impact on the level of sports participation, in addition to the social impact through social cohesion, and the psychological impact through self-esteem after participating in the Muscat Marathon experience. The Muscat Marathon also succeeded in placing a mental and emotional imprint on the participants. The study reached several recommendations, the most important of which is that local sports organizations organizing sporting events take care of such events in the current period, due to the lack of resources necessary to host huge events in the Sultanate of Oman.
Keywords: ماراثون مسقط -- الأنشطة الرياضية -- سلطنة عمان